Supersolidity in Rydberg tweezer arrays - Homeier, Lukas; Hollerith, Simon; Geier, Sebastian; Chiu, Neng-Chun; Browaeys, Antoine; Pollet, Lode (Physical review, 2025)
Rydberg tweezer arrays provide a versatile platform to explore quantum magnets with dipolar 𝑋𝑌 or van der Waals Ising 𝑍𝑍 interactions. Here, we propose a scheme combining dipolar and van der Waals interactions between two Rydberg states, where the amplitude of the latter can be greater than that of the former, realizing an extended Hubbard model with long-range tunnelings in optical tweezer arrays. On the triangular lattice with repulsive interactions, we predict the existence of a robust supersolid phase with a critical entropy per particle 𝑆/𝑁≈0.19 accessible in current Rydberg tweezer experiments supported by large-scale quantum Monte Carlo simulations. We further demonstrate the experimental feasibility by identifying pairs of Rydberg states in 87Rb realizing the required interactions. Such a lattice supersolid is long lived, found over a wide parameter range in an isotropic and flat two-dimensional geometry, and can be realized for hundreds of particles allowing one to directly probe the defect-induced picture of supersolids. Its thermodynamical and dynamical properties can hence be studied at a far larger scale than hitherto possible.
Gesehen am 16.12.2025